Hubungan Kesesuaian Penulisan Resep dengan FormulariumNasional Terhadap Mutu Pelayanan pada Pasien JaminanKesehatan Nasional di Rumah Sakit Umum di Bandung - Pratiwi, Winda Ratna; Kautsar, Angga Prawira; Gozali, Dolih (Pharmaceutical Sciences and Research, 2017)
Pharmaceutical service is one of the activities in hospital that support health service quality. One of the factors that can improve quality of pharmaceutical services is prescription services. In the era of National Health Insurance, prescription given to the patients should be based on the National Formulary. If prescriptions did not suit the national formulary, it would influence the services quality on pharmacy unit. The purposes of this study were to determine suitability of prescription outpatients’ national health insurance with national formulary and to determine the relationship of the suitability of prescription with a national formulary to service quality in pharmacy unit in one of general hospitals in Bandung. A cross sectional with servqual questionnaire was used to the patients and the 262 prescription samples needed were taken in January 2017. Mann Whitney test is used for bivariate analysis. The result indicated 91.7% prescriptions was suited the national formulary and the rest was not. There was a significant difference between prescription suitability with the national formulary to service quality in pharmacy unit in the hospital with p-value 0.00 (p < 0,05). It can be concluded that higher percentage of prescriptions suitability with the national formulary in hospital related with the better service quality of pharmacy unit.